Architecture and key technologies of network on demand for small and medium enterprises - Yuan ZHANG (Dianxin kexue)
The network on demand is mainly based on SDN,NFV and cloud technologies,which realizes the softening,automation and intelligence of the network and provides users with the ability to configure the network on demand.The architecture and key technologies of the network on demand were emphasized,and the collaborative orchestration was introduced.The SDN,NFV network and cloud resources were arranged,and the network path was quickly established by introducing the SD-WAN overlay technology,and four application scenarios of the network on demand for small and medium enterprises were proposed.Network on demand can provide customers with a new web experience of “visual” “on-demand” and “self-service”.